2020
DOI: 10.1016/j.jpeds.2019.12.003
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Depression in Adolescents and the Importance of Early Recognition

Abstract: ental health disorders are frequent during the developmental years, particularly in adolescents. The leading cause of disability in young people are neuropsychiatric conditions, which if left untreated may severely affect development, including educational and social achievements. It has been reported that 10%-20% of individuals experience a form of mental disorder during childhood and adolescence worldwide. 1 One-half of them arise by 14 years of age. 2 Among adolescent mental health disorders, depression is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 29 publications
0
40
0
1
Order By: Relevance
“…Важным фактором, обеспечивающим достоверность результатов, полученных из опросников, исследующих психические расстройства в целом и во время чрезвычайных ситуаций в частности, является процедура сбора данных и их статистического анализа. Использование стандартных статистических методов обеспечивает возможность сопоставить результаты с итогами других исследований [12,13].…”
Section: ранние исследования поведенческих и эмоциональных реакций киunclassified
“…Важным фактором, обеспечивающим достоверность результатов, полученных из опросников, исследующих психические расстройства в целом и во время чрезвычайных ситуаций в частности, является процедура сбора данных и их статистического анализа. Использование стандартных статистических методов обеспечивает возможность сопоставить результаты с итогами других исследований [12,13].…”
Section: ранние исследования поведенческих и эмоциональных реакций киunclassified
“…In addition, several studies found that the lockdown had resulted in more family conflicts and affected the parent-child relational experience, which influenced children’s well-being ( Spinelli et al, 2020 ). The risk is that these family conflicts will be expressed as a kind of violence against children, making them vulnerable to emotional damage ( Cluver et al, 2020 ; Jiao et al, 2020 ; Petito et al, 2020 ; Solantaus et al, 2004 ). As for the effect of children’s COVID-19-related nervousness on their psychological condition, the literature mentions that school-aged children are able, to some extent, to assess the crisis, familiar with the use of media, and aware of the negative information the media can convey ( Oppenheimer et al, 2016 ; White, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among adolescents, depression is one of the most common mental health challenges and a suicide risk factor, with onset usually in mid-to-late adolescence (Petito et al, 2020). It is critical to halt psychological distress and promote wellbeing among adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic psychological stress among adolescents has harmful impacts on neurobiological systems that are connected with emotional and behavioral regulation across the lifecourse (De Bellis, 2001). Without treatment, depression can harm educational and social outcomes, and may contribute to other health concerns such as smoking and substance use (Petito et al, 2020). Depression usually impacts youth during mid-to-late adolescence, hence identifying illness and early intervention can reduce the likelihood that adolescents will develop severe depression or other psychosocial challenges (Petito et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation